Dependence of the Blow-up Time with Respect to Parameters for Semilinear Parabolic Equations with Nonlinear Memory (Communications in Mathematical Research, 2021)
In this paper we discuss the bounds for the modulus of continuity of the blow-up time with respect to three parameters of $λ$, $h$, and $p$ respectively for the initial boundary value problem of the semilinear parabolic equation.
Keywords: nonlocal parabolic equation; nonlinear memory; blow-up time; bound.